The wired - Ali, S. (IEEE Communications magazine)
The networking infrastructure provided at the IEEE NOMS 2000 conference in Honolulu in April 2000 was a field trial of new electronic technologies and services for hotels, conference centers, and meeting events. Its essential elements were immediate and transparent network access, both wired and wireless physical access, and media services including an online database of keynote presentations, proceedings papers, and audio/visual multicasts. This article introduces the services concepts, the technology behind them, and the lessons learned from the NOMS 2000 field trial.